Scroll, Click, Apply: What Drives Millennials and Gen Z to Pursue Jobs Online? - Novita Herlissha; Tiara Fitari (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2025)
The era of digitalization has brought significant changes, especially in recruitment technology. Nowadays, job applications are increasingly conducted through digital platforms such as company websites and social media, supported by employer branding content. This study investigates the influence of e-recruitment on job application intention among 96 Millennial (Generation Y) and Generation Z individuals in Pangkalpinang City and Bangka Regency. Using purposive sampling and statistic analysis with Smart PLS 4.0, the study finds that: E-recruitment has a positive and significant effect on the intention of Generation Y to apply for jobs; E-recruitment also has a positive and significant effect on the intention of Generation Z to apply for jobs..